Thermal and spectroscopic studies on solid ibuprofen complexes of lighter trivalent lanthanides - Galico, D. A. [UNESP]; Holanda, B. B. C. [UNESP]; Guerra, R. B. [UNESP]; Legendre, Alexandre de Oliveira [UNESP]; Rinaldo, Daniel [UNESP]; Treu-Filho, O. [UNESP]; Bannach, Gilbert [UNESP] (Elsevier B.V., 2014)
Solid-state compounds of general formula Ln(L)(3), in which Lis ibuprofen and Ln stands for trivalent La, Ce, Pr, Nd, Sm and Eu, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), X-ray powder diffractometry (DRX), complexometry, Fourier-transformed infrared spectroscopy (FTIR) and thermogravimetry coupled to Fourier-transformed infrared spectroscopy (TG-FTIR) were used to characterize these compounds. The results provided information concerning the chemical composition, dehydration, coordination modes of the ligands, crystallinity of the samples, thermal behavior and thermal decomposition of the compounds. The theoretical and experimental spectroscopic studies suggest that ibuprofen coordinates through the carboxylate group as a chelating ligand. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Ibuprofen; Lanthanides; Carboxylate complexes; Thermal behavior; Infrared spectroscopy; TG-FTIR